1974
DOI: 10.1159/000122293
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Existence in Spermatozoa of a Factor Inhibiting the Follicle Stimulating Hormone Releasing Hormone Synthesis

Abstract: A peptidic factor, isolated from bull spermatozoa and previously described as inhibiting ovarian maturation, reduces the release of follicle stimulating hormone (FSH) in the male rat, when administered intraventricularly. This action is still evident at a dose level of 100 ng. It seems reasonable to postulate that the factor acts at the level of central nervous structures, because the follicle stimulating hormone releasing hormone (FSH-RH) hypothalamic content is also greatly decreased. However, luteinizing ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
2

Year Published

1978
1978
1991
1991

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 4 publications
1
12
0
2
Order By: Relevance
“…Following the discovery of follicle-stimulating hormone (FSH) and luteinizing hormone (LH), the two pituitary hormones known to regulate the development and activity of the gonads, Klinefelter et al (3) postulated that a testicular factor, inhibin, exerted a specific negative feedback action on pituitary FSH secretion. This hypothesis was substantiated when numerous investigators demonstrated a direct suppression of peripheral FSH in animals treated with steroid-free testicular or ovarian preparations (4)(5)(6). Inhibin activity has since been observed in testicular or ovarian extracts and in cultured Sertoli or granulosa cells from a variety of species (7)(8)(9)(10).…”
mentioning
confidence: 96%
“…Following the discovery of follicle-stimulating hormone (FSH) and luteinizing hormone (LH), the two pituitary hormones known to regulate the development and activity of the gonads, Klinefelter et al (3) postulated that a testicular factor, inhibin, exerted a specific negative feedback action on pituitary FSH secretion. This hypothesis was substantiated when numerous investigators demonstrated a direct suppression of peripheral FSH in animals treated with steroid-free testicular or ovarian preparations (4)(5)(6). Inhibin activity has since been observed in testicular or ovarian extracts and in cultured Sertoli or granulosa cells from a variety of species (7)(8)(9)(10).…”
mentioning
confidence: 96%
“…Additionally, it has been suggested that they may also act on the hypothalamus to indirectly regulate FSH secretion [12][13][14]. The presence of activin/inhibin pA and Pb subunit-stained terminals in the reReceived: September 20, 1990 Accepted after revision: March 4, 1991 gions of the septal and the preoptic areas, where neurons con taining GnRH are found, suggests that activin, and possibly in hibin, may act on the hypothalamus to regulate GnRH expres sion an d /o r secretion [15].…”
mentioning
confidence: 99%
“…It seems possible that inhibin acts at the pituitary as well as the hypothalamus level [74]. If inhibin acts on the pituitary, it should modulate the stimulation exerted by GnRH.…”
Section: Mode Of Action Of Inhibinmentioning
confidence: 99%
“…Lugaro et al [74] administered apeptidic factor isolated from bull spermatozoa into the lateral ventricle of castrated male rats, which suppressed serum FSH levels and GnRH activity, but not LH.…”
Section: Mode Of Action Of Inhibinmentioning
confidence: 99%